Climate as the Great Equalizer of Continental‐Scale Erosion. Issue 20 (19th October 2021) - Jepson, Gilby; Carrapa, Barbara; Gillespie, Jack; Feng, Ran; DeCelles, Peter G.; Kapp, Paul; Tabor, Clay R.; Zhu, Jiang
Abstract: Central Asia hosts the most extensive and highest topography on Earth, which is the result of the feedbacks among rock uplift, atmospheric circulation and moisture transport, and erosion. Here, we analyze 2, 511 published low‐temperature thermochronometric ages as a proxy of the regional‐scale erosion of Central Asia. We compare these ages to tectonic and climate proxies, and state‐of‐the‐art paleoclimate simulations to constrain the inﬂuences of climate and tectonics on the topographic architecture of Central Asia. We observe a ﬁrst‐order relationship between younger cooling ages in areas of high precipitation and older ages (Mesozoic) in areas that have been sheltered from precipitation, despite high strain rates. Thus, we suggest that climate enhances erosion in areas where rock uplift produces signiﬁcant orographic gradients, whereas in the continental interior, areas which are tectonically active but have been sheltered from signiﬁcant precipitation record older ages and a longer erosional history. Plain Language Summary: Modern topography represents the product of the relationships among climate, tectonics, and erosion through time. Central Asia is one of the most topographically diverse regions on Earth. However, the relative role of tectonics versus climate on erosion of continental Asia remains one of the major debates in Earth sciences. One way to investigate this is through the analysis of erosional proxies. In this study, we present the ﬁrst regional‐scale analysis of thermochronometric ages from Central Asia as a proxy of erosion. We compare these data to tectonic processes, climate proxies, and state‐of‐the‐art paleoclimate simulations in order to constrain the relative inﬂuences of climate and tectonics on the topographic architecture and erosion of Central Asia. There is a ﬁrst‐order relationship between more recent erosion and active tectonic boundaries. However, more recent erosion is also associated with areas of high precipitation, whereas areas that have been sheltered from signiﬁcant precipitation retain a signal of older erosional events. Thus, we suggest that climate plays a key role in enhancing erosion in areas with developed topography and high precipitation, whereas areas which experienced sustained aridity record less erosion and preserve a record of older erosion. Key Points: Despite the magnitude of the India‐Asia collision, erosion throughout Central Asia reﬂects Phanerozoic tectonics Regions of "old" erosion are preserved in more arid areas, whereas more recent erosion is concentrated in areas of high precipitation Tectonic mechanisms are required to initiate erosion; however, climate modulates the magnitude of erosion